Hadits Diseminasi Hadits Dimasyarakat - Jazelyna Afnida Nanda (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Hadith is one of the second sources of Islamic law after the Qor’an, where if there is a case that is not clear in the Koran, the hadith is the explanation. The existence of hadith among the general public is so important at this time, this is due to the lack of public understanding with the generality of the Koran. However, the dissemination of hadith now takes place without any filtering, where hadiths are useful for themselves and their group, so they are used, just like the hadith of maudhu'. Actually this is very unfortunate, because many hadiths that should be the reference of the people from the Prophet have been falsified. These maudhu' hadith are not only spread among the people, in fact many of them believe in these maudhu' hadith and practice them. maudhu' ittu is a lie that is deliberately based on the Prophet.